2013
DOI: 10.1309/ajcpywx49izsqkfs
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an External Quality Assessment Program for HIV Testing in Haiti, 2006–2011

Abstract: Objectives To evaluate an external quality assessment (EQA) program for human immunodeficiency virus (HIV) rapid diagnostics testing by the Haitian National Public Health Laboratory (French acronym: LNSP). Acceptable performance was defined as any proficiency testing (PT) score more than 80%. Methods The PT database was reviewed and analyzed to assess the testing performance of the participating laboratories and the impact of the program over time. A total of 242 laboratories participated in the EQA program … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 13 publications
1
25
1
Order By: Relevance
“…Because our study participants included all testing points and they performed HIV testing using HIV rapid test but their study participants' only laboratory professionals and they used HIV rapid test and ELISA to perform HIV rapid testing. Our findings demonstrated that 82.8% of testing points score 80 and above this lower than study conducted by Jean Louis and his colleagues which was 97.5% [14]. …”
Section: Discussioncontrasting
confidence: 60%
“…Because our study participants included all testing points and they performed HIV testing using HIV rapid test but their study participants' only laboratory professionals and they used HIV rapid test and ELISA to perform HIV rapid testing. Our findings demonstrated that 82.8% of testing points score 80 and above this lower than study conducted by Jean Louis and his colleagues which was 97.5% [14]. …”
Section: Discussioncontrasting
confidence: 60%
“…Most studies were carried out in Africa ( n  = 48) [5,7,1014,16,2225,29,30,3234,36,37,39,41,43,44,46,47,49,51,52,54–59,61–65,67–72,74,75], followed by in the Americas ( n  = 7) [28,31,42,50,53,60,66], Asia ( n  = 4) [8,35,45,73] and Europe ( n  = 1) [48]. There were also four multi-country/regional studies [26,27,38,40].…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-seven studies reported using a suboptimal testing strategy that differed from the WHO recommendations [5,8,1114,16,2230,3234,36–39,4244,49,51,53,59,62,64–66,68,72,75]. Suboptimal testing strategies included using a highly specific first-line test and highly sensitive second-line test [14,33,39,55], using a single RDT for HIV-positive diagnoses [11,66,72], using a high prevalence testing strategy in a low prevalence setting [16,49], using a parallel testing algorithms and a tiebreaker testing strategy (where a third assay is used to resolve discrepant test results and rule in HIV infection) [5,12,13,16,24,25,2730,32,34,36,37,68].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations